Proposals for the Implementation of a Comprehensive Inter-Departmental Approach in the Improving of Mechanisms for Organization of Education for Children with Disabilities - Klochko E.Y (Moscow State University of Psychology and Education, 2018)
The implementation of a comprehensive inter-agency approach for the organization of education for children with disabilities requires coordinated activities of educational structures, medico-social expertise, and social protection. A number of measures have been proposed for the development of uniform approaches to this issue of different departments and agencies and also for provision of mechanisms of continuity of the processes of children's education.